Analysis of Accountability and Transparency of Waqf Management in Realising the SDGs of Quality Education Points - Fatmawati, Fatmawati; Afifah, Azahra Nur; Aulia, Chairunnisa Shandy; Septiani, Sevira Wulan; Aditya, Aditya; Ramadhanti, Wita (Jurnal Akuntansi, Manajemen dan Ekonomi, 2024)
This study focuses on waqf, which specifically analyses the accountability and transparency of waqf management in accordance with PSAK 112 in realising the achievement of the Sustainable Development Goals (SDGs) on quality education points. This study uses qualitative methods with data collection techniques through interviews, observation, and documentation. The participants in this study were waqf management institutions in Banyumas Regency including Muhammadiyah, Nahdlatul Ulama, and Al-Irsyad. The results of this study, Nazir has not fully understood and implemented PSAK 112. Waqf has also played a role in realising quality education, although it is still limited to waqf of immovable objects in the form of land used by educational institutions in Banyumas Regency. Policy implications include the need for outreach, training and coaching to Nazirs regarding the implementation of PSAK 112 so that waqf management can be more productive and quality education can be realised. This study implies that accountability and transparency play a role in realising the SDGs of quality education.